2019
DOI: 10.4155/fmc-2019-0130
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Sphingosine Kinase 1 for the Treatment of Pulmonary Arterial Hypertension

Abstract: Pulmonary arterial hypertension (PAH), characterized by high morbidity and mortality, is a serious hazard to human life. Until now, the long-term survival of the PAH patients is still suboptimal. Recently, sphingosine kinase 1 (SPHK1) has drawn more and more attention due to its essential role in the pulmonary vasoconstriction, remodeling of pulmonary blood vessels and right cardiac lesions in PAH patients, and this enzyme is regarded as a new target for the treatment of PAH. Here, we discussed the multifariou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 98 publications
0
4
1
Order By: Relevance
“…SphK1/S1P has been reported to mediate TGF-β1-induced proliferation in rat PASMCs (Wang et al, 2019), however, we did not observe a significant pro-proliferative effect of TGF-β1 in human PASMC (Figure S4). This highlights potential differences between the responses of rat and human PASMCs to the same stimuli.…”
Section: Discussioncontrasting
confidence: 74%
See 1 more Smart Citation
“…SphK1/S1P has been reported to mediate TGF-β1-induced proliferation in rat PASMCs (Wang et al, 2019), however, we did not observe a significant pro-proliferative effect of TGF-β1 in human PASMC (Figure S4). This highlights potential differences between the responses of rat and human PASMCs to the same stimuli.…”
Section: Discussioncontrasting
confidence: 74%
“…It required deletion of SphK1 and SphK2 to completely abolish the production of S1P and inhibit the effect of S1P (Meng, Yuan, & Lee, 2011;Mizugishi et al, 2005;Xiong et al, 2013). This could explain the less significant inhibitory effect of PF-543 on TGF-β-induced αSMA expression, since PF-543 might not fully block the function of SphK2 at 10 µM (Yang, Jiang, Xu, Song, & Wang, 2019). Overall, these findings still suggest that SphK1 is important for regulating TGF-β-induced αSMA expression and that CNN1 expression is not completely dependent on S1P signaling.…”
Section: Sphk1 Inhibitors Reduce Tgf-β-induced αSma Expressionmentioning
confidence: 99%
“…It has been proved that SphK1 is involved in the occurrence of pulmonary arterial hypertension (PAH) based on the over-expression of SphK1 in vascular smooth muscle cells (VSMC) and lymphocytes of patients with PAH, and the symptoms of PAH were alleviated in SphK1 knockout mice rather than SphK2 ( Pyne and Pyne, 2017 ; Yang et al, 2019 ). Thus, SphK1/S1P signaling is a novel pathway in the inflammatory mechanism of PAH.…”
Section: Role Of Sphingosine Kinase 1 In Inflammatory Immune Related-diseasesmentioning
confidence: 99%
“…Wang et al [42], Mishra et al [43], Deaton et al [44] and You et al [45] demonstrated that altered expression of SPHK1, WDR13, GIGYF1 and DNMT3A were found to be substantially related to type 2 diabetes mellitus. Altered expression of SPHK1 [46] was easily found in hypertension. Recently, increasing evidence demonstrated that SPHK1 [47] and DNMT3A [48] were altered expression in cognitive diseases.…”
Section: Discussionmentioning
confidence: 99%